\(Schizostachyum locbacense \) (Poaceae: Bambusoideae), a new species from southern Vietnam - Tien Tran, Van (Academia Journal of Biology, 2022)
Schizostachyum locbacense sp. nov. from Vietnam is described and illustrated. It is recognized from southern Vietnam, where it occurs at 1,033 m in Loc Bac commune, Bao Lam district, Lam Dong province. Based on its vegetative, inflorescence, and basic spikelets structures, Schizostachyum locbacense is closely similar to Schizostachyum brachycladum and Schizostachyum langbianense, but differs from S. brachycladum by internode 3–5 cm diam, culm leaf abaxial white hairs, auricles inconspicuous or replaced by a low dark thickened rim to ca 1 mm high, rhachilla extension less than 1/2 length of the lemma, lodicules 2; from S. langbianense by 2 perfect flowers.